2016
DOI: 10.18016/ksujns.21217
|View full text |Cite
|
Sign up to set email alerts
|

Akdeniz Meyve Sineğinin Feromon Tuzaklarla (Ceratitis capitata Wied.) (Diptera: Tephritidae)’nin Nar ve Hurmadaki Populasyon Takibi ve Zarar Oranının Tespiti

Abstract: Bu çalışma 2015 yılında Adana ilinde trabzon hurma (Rojo brillante) çeşidi ve nar (Acco) çeşidinin bulunduğu bahçelerde yürütülmüştür. Çalışmada; Akdeniz meyve sineği (Ceratitis capitata Wied.) (Diptera: Tephritidae)'nin nar ve trabzon hurması çeşidindeki popülasyon gelişimleri ve meyvedeki zarar oranının belirlenmesi amaçlanmıştır. Akdeniz meyve sineğinin popülasyon gelişimi SEDQ sarı tuzak+feromon (cezbedici+insektisit) kullanılarak yapılmıştır. Popülasyon takibi sonucu tuzaklarda yakalanan Akdeniz meyve sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although Demirel (2014) reported that the infestation rates in pomegranate orchards was between 3-43.5% according to varieties of pomegranate. Kasap and Aslan (2016) indicated that the infestation rates in pomegranate was 1.35% in date was 5.2% in Adana province.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although Demirel (2014) reported that the infestation rates in pomegranate orchards was between 3-43.5% according to varieties of pomegranate. Kasap and Aslan (2016) indicated that the infestation rates in pomegranate was 1.35% in date was 5.2% in Adana province.…”
Section: Discussionmentioning
confidence: 94%
“…As a result of the study conducted in Konya, depending to the climatic conditions in the peach orchards, the pest formed 2 to 4 peak in the season. Tiring and Satar (2017) reported that this pest has 7-8 generations in avocado, fig and peach orchards in Balcalı (Adana), Başpınar et al (2009) detected 4-5 generations in the province of Aydin in citrus orchards, Kızılyamaç (2016) determined 3-7 generations at different elevations; Kasap and Aslan (2016) reported, 5-6 generations in the persimmon and 6-7 generations in the pomegranate orchards in Adana province. As a result of all these studies, it was stated that the pest has a large number of generation in different hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Yıldırım & Başpınar (2011) found that infestation rate of Total sampled fruits Total damaged fruits pomegranate orchards during the harvest was 2.20 percent. Furthermore, Kasap & Aslan (2016) reported that the infestation rates of medfly on Acco pomegranate was 5.2% in Adana province.…”
Section: Resultsmentioning
confidence: 99%